A comparative analysis of the short-term memory of martial arts` athletes of different level of sportsmanship - Romanenko, V.; Podrigalo, L.; Cynarski, W. J.; Rovnaya, O.; Korobeynikova, L.; Goloha, V.; Robak, I. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Problem. The paper presents a comparative analysis of the short-term memory of martial arts players and involved 45 participants in the martial arts (taekwondo, karate, judo, sambo, Greco-Roman wrestling) with different levels of skill. Material and Method. The 1st group included 17 male athletes, average age 16.88±0.48, who were general athletes and novice sportsmen. The 2nd group was 14 strong, aged 19.50±2.43, athletes of First Class Sportsman (regional champion) rank while the 3rd group of 14 was aged 19.57±0.40 and had a high degree of training and experience, being Candidate Masters of Sport (national rank) and Masters of Sport (national champion) rank. Their short-term memory was tested using the «TestSTMemory» computer application and their heart rate was monitored at the same time. To note the heart rate (HR) a BT4.0&ANT+ HR monitor was used. Results. It was found that results depend on levels of skill. During the later stages of the test the HR of novice sportsmen was notably higher. In carrying out the test the First Class Sportsman athletes showed a lower number of accurate clicks. Masters athletes completed the test much faster, and the average duration of their attempts in the 3rd stage of testing was shorter. These athletes also made far fewer errors during the 1st/2nd stages of testing. A lower rate of average and minimum HR was found in Masters athletes as compared with the First Class Sportsman group. The Masters athletes carried out the test with increased efficiency, i.e. the amount of correct clicking was higher, than with novice sportsmen. During the 2nd/3rd phases they made significantly fewer errors. Masters athletes carried out the final stage of the test faster than the novice sportsmen. The reduction in the initial, average and minimum HR in Masters athletes displays how the organism is activated to promote economy and higher psychological stability. This hypothesis is confirmed by the HR results during the 2nd/3rd test phases. Conclusions. The results obtained confirmed greater stress adaptation among novice sportsmen. Masters athletes had a higher level of short-term memory and a greater ability to process information rapidly. Masters athletes showed a higher degree of workability, and the best ability to mobilise and economise bodily functions.